From coal to variable renewables: Impact of flexible electric vehicle charging on the future Indian electricity sector. (15th April 2023) - Shu, Tony; Papageorgiou, Dimitri J.; Harper, Michael R.; Rajagopalan, Srinivasan; Rudnick, Iván; Botterud, Audun
Abstract: India ranks third globally in overall greenhouse gas (GHG) emissions, with power and transportation first and third, respectively, in terms of India's sectoral GHG contributions. Motivated by India's Nationally Determined Contribution goals and stated intent to drive renewables growth and vehicle electrification, this paper explores the connections between India's power and road transportation sectors by investigating the benefits of flexible electric vehicle (EV) charging on a set of hypothetical 2037 Indian power grid infrastructures. Using two production cost models, one simulating optimal unit commitment and hourly dispatch of available generation, the other simulating subhourly real-time dispatch operations, we examine the impact of flexible and inflexible EV charging regimes and vehicle-to-grid integration on generation profiles, peak load shaving, energy storage utilization, and overall emissions. Our techno-economic analysis shows that a number of future grid infrastructure scenarios, despite not specifically accounting for EV growth scenarios, may meet annual and hourly peak demand when combined with flexible EV charging; in contrast, inflexible EV charging, particularly during the early morning, will lead to substantial need for additional generation capacity. Coupled sectoral decarbonization remains tied to the grid generation mix, highlighting the need for continued policy focus on decarbonization of the rapidly growing power sector. Highlights: Flexible charging, grid decarbonization policies critical for EV adoption benefits. Scenario analysis highlights pathways to efficiency gains + emissions reductions. We quantify net CO2 emissions from power + road transport with increasing EV load. V2G reduces unserved reserves, prevents price spikes during extreme power outages.